On the rule of law and the quality of the law: reflections of the constitutional-turned-international judge - Küris, Egidijus (Teoría y Realidad Constitucional, 2019)
Western legal tradition gave the birth to the concept of the rule of law. Legal theory and constitutional justice significantly contributed to the crystallisation of its standards and to moving into the direction of the common concept of the rule of law. The European Court of Human Rights uses this concept as an interpretative tool, the extension of which is the quality of the law doctrine, which encompasses concrete requirements for the law under examination in this Court, such as prospectivity of law, its foreseeability, clarity etc. The author of the article, former judge of the Lithuanian Constitutional Court and currently the judge of the European Court of Human Rights, examines how the latter court has gradually intensified (not always consistently) its reliance on the rule of law as a general principle, inherent in all the Articles of the European Convention on Human Rights, to the extent that in some of its judgments it concentrates not anymore on the factual situation of an individual applicant, but, first and foremost, on the examination of the quality of the law. The trend is that, having found the quality of the applicable law to be insufficient, the Court considers that the mere existence of contested legislation amounts to an unjustifiable interference into a respective right and finds a violation of respective provisions of the Convention. This is an indication of the Court’s progressing self-approximation to constitutional courts, which are called to exercise abstract norm-control. La tradición occidental alumbró la noción del Estado de Derecho. La teoría del Derecho y la Justicia Constitucional han contribuido decisivamente a la cristalización de sus estándares, ayudando a conformar un acervo común en torno al mismo. El Tribunal Europeo de Derechos Humanos emplea la noción de Estado de Derecho como una herramienta interpretativa, fundamentalmente centrada en la doctrina de la calidad de la ley, que implica requisitos concretos que exige el Tribunal tales como la claridad, la previsibilidad, y la certeza en la redacción y aplicación de la norma. El autor, en la actualidad Juez del Tribunal Europeo de Derechos Humanos y anterior Magistrado del Tribunal Constitucional de Lituania, examina cómo el primero ha intensificado gradualmente (no siempre de forma igual de consistente) su confianza en el Estado de Derecho como principio general, inherente a todos los preceptos que forman el Convenio Europeo de Derechos Humanos, hasta el punto de que en algunas de sus resoluciones se concentra no tanto en la situación de hecho del demandante individual sino, sobre todo y ante todo, en el examen de esa calidad de la ley. La tendencia del Tribunal es a considerar que, si observa que la ley no goza de calidad suficiente, la mera existencia de la legislación discutida supone una interferencia injustificable dentro del derecho en cuestión y declara la violación del precepto correspondiente del Convenio. Esto implica el acercamiento progresivo del Tribunal Europeo de Derechos Humanos a los Tribunales Constitucionales, quienes tienen encargado el control en abstracto de la norma legal.